Diskursus dan Aktor dalam Pembuatan dan Implementasi Kebijakan Kehutanan: Masalah Kerangka Pendekatan Rasional (Discourses and Actors in the Forest Policy Formulation: Problems of Rational Framework) - Hariadi Kartodihardjo (Jurnal Manajemen Hutan Tropika, 2008)
This study was conducted to acquire how forest policy making process and implementation have been going on. The role of discourses, knowledge, actors and their networks determine effectiveness of policy debate to meet its goal. Forest policy making process and implementation was not occurred in a linear process as constructed in the rational framework. Imperfected knowledge creates dispute resolution. Effective interaction among actors to solve their diverse perception was determined by knowledge as well as discourses. The strength of actors and their networks and gap of their interest are significant factors to meet their agreed solution. The facts of forest policy process and implementation are expected to be understood by stakeholders and they should bear in mind that effort to improve performance of forestry development based on implementation of existing policy and policy reform remain unpredictable. This analysis are also expected to be used by stakeholders to get better policy intervention strategy.